Laparoscopic ovarian transposition in patients with pelvic cancer - Žilinskas, Kastytis; Sabonytė-Balšaitienė, Živilė; Samalavičius, Narimantas Evaldas (Acta medica Lituanica, 2014)
Background. The aim of this study was to evaluate the feasibility of laparoscopic ovarian transposition prior to radiation therapy on the preservation of hormonal function in the treatment of pelvic cancer. Materials and methods. A chart review of premenopausal women diagnosed with pelvic cancer, who underwent laparoscopic ovarian transposition to paracolic gutters, then received preoperative radiotherapy at the Center of Oncosurgery, Oncology Institute of Vilnius, from January 2010 to July 2013. Results. A total of 14 patients underwent laparoscopic ovarian transposition. Patients were divided into two groups by localisation of cancer: 2 (14.29%) patients diagnosed with rectal cancer and 12 (85.71%) with cervical cancer. Patients’ age was from 24 to 42  years with a mean age of 33.71 (SD  ±  5.22) years. The average age of the patients in the first group was 26 (SD ±  2.83) years. In the second group women, aged 29 and 42 years with a mean age of 35 (SD ± 4.35) years, were analyzed. Rectal cancer of stage III was diagnosed in both women of the first group. Tumor stage distribution in the second group, respectively: stage I  –  2  cases (16.67%), stage  II  –  3  cases (25%), stage  III  –  7 cases (58.33%). Seven (58.33%) patients of the second group underwent complete endoscopic staging. In these groups of 14 patients there were 2 (14.3%) complications (injury of the inferior vena cava and postoperative abnormal vaginal bleeding). No postoperative exitus occurred. The mean duration of the operation was 2 hours 26 minutes ± 55 minutes (60–245 minutes), respectively, 2  hours 40  minutes  ±  49  minutes (95–245  minutes) when laparoscopic staging and ovarian transposition was performed and 2  hours 12  minutes  ±  1  hour 1  minute (60–245  minutes) when only ovarian transposition was performed. The hospitalization period ranged from 5 to 52 days (average 12 days). Conclusions. Laparoscopic ovarian transposition is a relatively safe and effective procedure for preserving ovarian function. This procedure should be considered in all reproductive age female patients who need to undergo pelvic irradiation as part of pelvic cancer treatment.